Effect of weed management practices on nutrient uptake and productivity of wheat (Triticum aestivum) - KUMAR, BRAJESH; HASANAIN, MOHAMMAD; RAZA, M D BASIT; YADAV, R B; SINGH, RAJIV KUMAR; MISHRA, RISHABH; AHMAD, GUFRAN; SINGH, DIGVIJAY (The Indian Journal of Agricultural Sciences, 2022)
The study was undertaken to devise an efficient herbicide treatment combination for efficient weed control and higher yield and nutrient uptake. A field experiment was conducted to evaluate the performance of different herbicides for weed control and increasing yield as well as nutrient uptake in wheat (Triticum aestivum L.) at Meerut, Uttar Pradesh, during rabi season in 2016–17. The commonly used herbicides for restricting weed growth in wheat crop were taken in various combinations and appropriate doses. The study comprised 12 treatments (3 replications), of which 10 treatments were of various herbicidal combinations while the rest 2 were weed free and weedy checks. The weed control measure that involved Sulfosulfuron +Metsulfuron-methyl @20+2 g a.i/ha was found to be an efficient weed control measure that satisfactorily enhanced nutrient uptake and gave highest yield among various treatment combinations. The total biological yield of wheat in this treatment was around 1.4 times higher than that of weedy check. Therefore, the post emergence application of sulfosulfuron and metsulfuronmethyl @20+2 g a.i/ha can be an effective measure for weed control giving a higher productivity and nutrient uptake in wheat crop. The results were even comparable to that of weed free plots. The treatment showed an increase of 88.25%, 63.37%, 74.73%, and 43.36% increase in total N, P, K uptake and biological yield, respectively, and therefore may be recommended.